Strategi Pemanfaatan Media Sosial Tiktok Sebagai ?Sarana Promosi di Perpustakaan Universitas Airlangga - Salma Salma (IJAL (Indonesian Journal of Academic Librarianship), 2024)
This research aims to find out the strategy for using TikTok social media as a promotional tool in the Airlangga University Library. The research method uses qualitative and case study methods. The focus of the research is the strategy for using TikTok social media as a promotional tool at the Airlangga University Library. The sampling technique chosen was Non-Probability Sampling, determining informants using purposive sampling, namely 2 TikTok social media management officers with 1 TikTok social media user, 6 TikTok social media users Airlangga University Library. Data collection techniques are interviews, observation and documentation. Airlangga University Library has succeeded in implementing the strategy of using TikTok social media as a means of promotion well with the strategy of (1) sharing TikTok video links on other social media which has increased engagement and disseminated information more widely. (2) collaborating with students as video talent, making videos more interesting and for contributing and learning. (3) Use of music and hashtags that are currently viral, attract attention, create fun transitions, and increase the potential for content to go viral. (4) upload videos at night. that upload times can affect engagement levels and viewership. (5) Use of live, playlist, like, comment, save and pinned features to help users search for and receive information efficiently. So, it can be concluded that the strategy of using TikTok social media by the Airlangga University Library has had a positive impact in expanding reach, increasing participation, and conveying library information in an interesting and relevant way for students.